Comparison of wind characteristics at different heights of deep-cut canyon based on field measurement. Issue 2 (January 2020) - Zhang, Jingyu; Zhang, Mingjin; Li, Yongle; Fang, Chen
The typical U-shaped deep-cut canyon is widely distributed in the western mountainous areas of China, especially in Sichuan province and Yunnan province. The deep-cut canyon has the characteristics of the high drop in elevation, high-temperature difference, and complex wind environment. A 50 m high meteorological mast with a total of eight anemometers was erected in such topography, and a long-span suspension bridge will be constructed in the area where the meteorological mast is located. Based on the long-term monitor data, the wind characteristic parameters including average and fluctuating wind characteristics and coherence between different heights are investigated. The results are as follows. The dominant wind direction which depends on the topography is north–south. The attack angle of wind is mainly less than zero, and its probability distribution obeys the hypothetical Gaussian distribution. Both the increases in height of anemometer and in wind speed reduce the dispersion of the attack angle of wind. The gust factor has a similar change law of attack angle of wind. Turbulence intensities are affected by the height of the anemometer and the wind speed, and they are different from the recommended value of China Codes. In terms of turbulence integral length scale, the value increases with an increase in the height of the anemometer in the same component. The largest value occurs in the longitudinal direction and the smallest occurs in the vertical direction at the same level. The coherence between any two locations is relatively strong, and the longitudinal component is stronger than others. The measured wind power spectrum for longitudinal, lateral, and vertical wind in deep-cut canyon fits the von Kármán model better.